Meltwater runoff in a changing climate (1951–2099) at Chhota Shigri Glacier, Western Himalaya, Northern India - Markus Engelhardt; Paul Leclercq; Trude Eidhammer; Pankaj Kumar; Oskar Landgren; Roy Rasmussen (Annals of Glaciology, 2017)
Meltwater runoff in the catchment area containing Chhota Shigri glacier (Western Himalaya) is simulated for the period 1951–2099. The applied mass-balance model is forced by downscaled products from four regional climate models with different horizontal resolution. For the future climate scenarios we use high resolution time series of 5 km grid spacing, generated using the newly developed Intermediate Complexity Atmospheric Research Model. The meteorological input is downscaled to 300 m horizontal resolution. The use of an ice flow model provides annually updated glacier area for the mass-balance calculations. The mass-balance model calculates daily snow accumulation, melt, runoff, as well as the individual runoff components (glacial melt, snowmelt and rain). The resulting glacier area decreases by 35% (representative concentration pathway (RCP) 4.5 scenario) to 70% (RCP 8.5 scenario) by 2099 relative to 2000. The average annual mass balance over the whole model period (1951–2099) was –0.4 (±0.3) m w.e. a–1. Average annual runoff does not differ substantially between the two climate scenarios. However, for the years after 2040 our results show a shift towards earlier snowmelt onset that increases runoff in May and June, and reduced glacier melt that decreases runoff in August and September. This shift is much stronger pronounced in the RCP 8.5 scenario.